BUILDING A FRAMEWORK FOR BUSINESS VISIBILITY OF MALAYSIAN SMES THROUGH SEARCH ENGINE OPTIMIZATION (SEO): A CONCEPTUAL PAPER - Zuraimi, Nur Zulaikha; Jaini, Azila (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Search Engine Optimization and digital capabilities have emerged as critical drivers for enhancing business visibility and achieving sustainable growth among Malaysian Small and Medium-sized Enterprises, which often face resource constraints in competitive digital landscapes. However, a critical research gap persists across theoretical, SEO is frequently relegated to a technical tactic rather than being integrated as a strategic resource within the Resource-Based View. Contextually, while SMEs comprise 98.5% of Malaysian establishments and contribute 38.9% to the GDP, they face a "30% adoption paradox" where only a minority utilize SEO despite high internet penetration (88.7%) and severe resource constraints, such as 81% of firms having cash flow for only three months. Grounded in the Resource-Based View, this conceptual study positions SEO as a strategic resource amplified by firm-specific digital capabilities to enhance business visibility and foster long-term growth. Through a systematic synthesis of literature on SEO, digital marketing, SME performance, and the Malaysian context, the paper proposes a conceptual framework elucidating the moderating role of digital capabilities in the relationship between SEO utilization and business visibility, which collectively drive sustainable growth. Theoretically, it extends RBV to SEO and digital domains, offering a conceptual groundwork for empirical validation and practical guidance for Malaysian SMEs.